Evaluation of water quality of mangrove ecosystems of Kundapura, Udupi district, Karnataka, Southwest coast of India. - Kumara, Vijaya; K.M, Vijaya Kumar (Journal of Ecobiotechnology, 2012)
The present study was carried out to evaluate the physico-chemical parameters of four selected sites of mangrove ecosystem, located at Kundapura, of Udupi district, Karnataka, Southwest coast of India, for a period of one year from August-2010 to July-2011. The physicochemical parameters play a vital role in the mangrove ecosystems. A seasonal variation in these parameters was observed throughout the study period and monthly comparisons were made as monsoon, pre-monsoon and post-monsoon. The results of the present investigations are compared with literature values and investigation reveals that there is a fluctuation in the physico-chemical characters of the water, this will be due to ebb and flow and change in the temperature and salinity as season changes.